2020
DOI: 10.1111/coa.13607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of exclusive endoscopic tympanoplasty with porcine small intestine submucosa in 72 patients

Abstract: Tympanoplasty is a technique that uses grafting materials to repair the tympanic membrane perforation through various approaches, including endaural, permeatal and retroauricular. Numerous grafting materials, such as autografts, allografts and xenografts, can be used. 1-3 Autografts, such as temporalis fascia, fat, loose connective tissue, perichondrium and cartilage, have been applied. 4-6 Additionally, al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Yawn et al had a 77.3% closure rate for primary surgery with pSIS and 100% after a single revision in a group of adult and pediatric patients, the majority of whom had concomitant cartilage grafting 6 . Additionally, Chen et al similarly noted a closure rate of 94.7% with pSIS in an adult population 18 . Similarly high closure rates were found in both the pediatric and adult populations for primary isolated tympanoplasty.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Yawn et al had a 77.3% closure rate for primary surgery with pSIS and 100% after a single revision in a group of adult and pediatric patients, the majority of whom had concomitant cartilage grafting 6 . Additionally, Chen et al similarly noted a closure rate of 94.7% with pSIS in an adult population 18 . Similarly high closure rates were found in both the pediatric and adult populations for primary isolated tympanoplasty.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of patients also received a concomitant cartilage graft, which may have influenced the graft take rate 6 . Chen and Hsieh also found a high closure rate with pSIS in an adult population with TM perforation related to simple chronic otitis media 18 . Both of these studies reported significant improvement in postoperative air–bone gap (ABG) 6,18 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the one-handed surgical technique in particular might benefit from the more rigid grafting material, as its correct placement may be facilitated. This might also be the reason for the promising results of porcine small intestine submcosa grafting in endoscopic tympanoplasty type I with GIR of 94.7% and significant ABG improvement of 7.2 dB 24 . Further reduced donor-site morbidity and additional reduction of operation time due to graft harvesting are the considerable advantages of this method.…”
Section: Discussionmentioning
confidence: 96%